Efektifitas Media Peta Konsep Untuk Meningkatkan Hasil Belajar Kimia Umum I Mahasiswa Program Studi Pendidikan Matematika Pada Materi Stoikiometri - Freddy Tua Musa Panggabean; Nora Susanti (Pascasarjana Universitas Negeri Medan, 2015)
Abstract. Chemistry is very appropriate if taught using chemistry concepts with attractive appearance so it is easy to understand. So that students can be attracted and interested in learning the concepts of chemistry and can improve student learning outcomes are achieved, one way to do lecturer is by applying the concept of learning to use the concept map media. In this study a comparison between groups of students who were learning with media concept map with a group of students who were learning without media concept map. Results of the study proved that learning with concept maps media effectively used in improving student learning outcomes and interest study program mathematics FMIPA UNIMED in following the general chemistry course-I on learning stoichiometry. The average increase in learning outcomes (gain scores) students are given learning with concept maps media (lesson-1 = 0.67±0.20; lesson-2 = 0.68±0.16; lesson-3 = 0.79±0.15; and the overall lesson = 0.71 ± 0.11) higher than the average increase in learning outcomes (gain scores) students are given learning without media concept map (lesson-1 = 0.50±0.20; lesson-2 = 0.58±0.16; lesson-3 = 0.62±0.14; and the overall lesson = 0.57±0.11). Similarly, with an average increase in interest in learning (gain score interests) students are given learning with media concept map (0.46±0.10) was higher than the average increase in interest in learning (gain scores interest) given student learning without media concept maps (0.23±0.11). Keywords: concept map, interest, learning outcomes